Reconstruction of Cyber Policing Law in the Prevention and Enforcement of Online Gambling through the Integration of Cyber Supervision and Digital Community Protection in Indonesia - Iwan Matthew Frans Kapojos; Yundini Husni; Kif Aminanto (Journal Customary Law, 2026)
The development of Indonesia's digital society has driven the transformation of conventional crime into modern cybercrime, one of which is online gambling, which has grown massively, anonymously, and transnationally through the use of information technology, social media, financial technology, cryptocurrency, and cross-border digital platforms. This study examines weaknesses in the legal framework and challenges in implementing cyber policing in the prevention and prosecution of online gambling in Indonesia. It also seeks to develop a reconstruction of cyber policing law through the integration of cyber surveillance and digital community protection. The research adopts a normative juridical method using statutory and conceptual approaches, analyzing various legal instruments, including the Criminal Code, the Electronic Information and Transactions Law, the Police Law, the Personal Data Protection Law, as well as relevant legal doctrines and theories. The results of the study indicate that the Indonesian legal system still has normative weaknesses, such as the absence of specific cyber policing regulations, weak regulations on cyber surveillance and digital evidence, limited cyber jurisdiction, and the suboptimal integration of digital transactions and cyberspace supervision between state institutions. The implementation of cyber policing also faces obstacles in the form of limited cyber investigators, minimal digital forensics infrastructure, weak cyber intelligence, and the low use of artificial intelligence in cyber surveillance. Therefore, a reconstruction of cyber policing law is needed through the establishment of comprehensive national regulations, strengthening of an integrated cyber monitoring system, the establishment of a national cyber command center, strengthening predictive policing based on artificial intelligence, harmonizing cross-sectoral regulations, and strengthening international cooperation to create a digital law enforcement system that is preventative, integrative, adaptive, and based on protecting the digital community in Indonesia.